Status gizi dan motivasi belajar sebagai faktor risiko terhadap kemampuan kognitif anak sekolah dasar di daerah endemik GAKY - Agnesia, Dian; Sudargo, Toto; Widodo, Untung Supariadi (Jurnal Gizi dan Dietetik Indonesia (Indonesian Journal of Nutrition and Dietetics), 2013)
ABSTRACTBackground: More than 200 million children under 5 years old in developing countries are not fulfilled its development potential. Child potential development is influenced by several factors, such as biological factors, psychosocial, physical, social, culture, and socio-economic. People living in iodine deficiency area have intelligent quotient (IQ) up to 13.5 point lower than those living in the area with suffi cient iodine. The result of iodinized salt monitored by Sleman District Health Offi ce showed total goitre rate (TGR) of school children in Subdistrict of Cangkringan, District of Sleman was 39.5, which was categorized as severe iodine deficiency.Objective: To identify nutritional status (anthropometry), academic achievement, and learning motivation as risk factors of cognitive ability of elementary children in IDD endemic area.Method: The study used case control design. Samples consisted of 107 children with cognitive ability below average (score IQ<90) as cases and 198 children with cognitive ability above average (score IQâ‰¥90) as controls. Data of cognitive ability were obtained through culture fair intelligence test (CFIT), anthropometric assessment for nutritional status, clean score of Indonesian and mathematics for academic achievement, and questionnaire for learning motivation of children. Data were processed descriptively and analytically using chi-square and t-test.Result: The prevalence of short nutritional status was 25.9%. There was signifi cant association between nutritional status (height/age) (p=0.46), learning motivation (p=0.03), and academic achievement (Indonesian, p=0.00, mathematics, p=0.000), and cognitive ability. There was no association between nutritional status (Body Mass Index/age) and cognitive ability (p=0.109). Children with short nutrition status had risk 1.7 times greater for lower cognitive ability. Children with low learning motivation had risk 3.3 times greater for low cognitive ability.Conclusion: Children with cognitive ability above average had nutritional status (height/ age), learning motivation, and academic achievement (Indonesia and mathematics) better than those with cognitive ability below average.KEYWORDS: cognitive, nutritionl status, learning motivation, academic achievement, iodine deficiency disorderABSTRAKLatar belakang: Lebih dari 200 juta anak di bawah 5 tahun di negara berkembang tidak terpenuhi potensi perkembangannya. Potensi perkembangan anak dipengaruhi oleh beberapa faktor, yaitu faktor biologis, psikososial, fisik, sosial budaya serta, sosial ekonomi. Masyarakat yang tinggal di daerah defisiensi iodium memiliki intelligent quotient (IQ) hingga 13,5 point lebih rendah dibandingkan masyarakat yang tinggal di daerah cukup yodium. Hasil pemantauan garam beryodium oleh Dinas Kesehatan Sleman menunjukkan total goitre rate (TGR) anak sekolah di Kecamatan Cangkringan Kabupaten Sleman adalah 39,5%, yang tergolong dalam endemik berat.Tujuan: Mengetahui bahwa status gizi (antropometri), prestasi belajar, dan motivasi belajar sebagai faktor risiko terhadap kemampuan kognitif anak sekolah dasar di daerah endemik GAKY.Metode: Jenis penelitian adalah studi kasus kontrol. Jumlah subjek penelitian yaitu kelompok kasus 107 anak dengan kemampuan kognitif di bawah rata-rata (skor IQ<90) dan kontrol 198 anak dengan kemampuan kognitif di atas rata-rata (skor IQ>90). Pengumpulan data kemampuan kognitif dengan menggunakan culture fair intelligence test (CFIT), pengukuran antropometri untuk status gizi, nilai murni Bahasa Indonesia dan matematika untuk prestasi belajar dan kuesioner untuk motivasi belajar anak. Data diolah secara deskriptifanalitik menggunakan uji chi-square dan uji beda t-test.Hasil: Prevalensi status gizi pendek sebesar 25,9%. Terdapat hubungan signifi kan antara status gizi (TB/U) (p=0,046), motivasi belajar (p=0,03), dan prestasi belajar (Bahasa Indonesia, p=0,00, matematika, p=0,00) dengan kemampuan kognitif. Tidak terdapat hubungan signifi kan antara status gizi (IMT/U) dengan kemampuan kognitif (p=0,109). Anak dengan status gizi pendek berisiko 1,7 kali memiliki kemampuan kognitif di bawah rata-rata daripada anak normal. Anak dengan motivasi rendah berisiko 3,3 kali memilikikemampuan kognitif di bawah rata-rata.Kesimpulan: Anak dengan kemampuan kognitif di atas rata-rata memiliki status gizi, motivasi belajar, dan prestasi belajar (Bahasa Indonesia maupun matematika) yang lebih baik daripada yang memiliki kemampuan kognitif di bawah rata-rata.KATA KUNCI: kognitif , status gizi, motivasi belajar, prestasi belajar, endemik GAKY